Diabetic kidney disease: An overview of prevalence, risk factors, and biomarkers - Salman Hussain; Mohammad Chand Jamali; Anwar Habib; Md Sarfaraj Hussain; Mohd Akhtar; Abul Kalam Najmi (Clinical Epidemiology and Global Health, 2021)
Diabetic kidney disease (DKD) is a major public health problem characterized by elevated urine albumin excretion or reduced glomerular filtration rate or both. The pathophysiology of DKD involves various pathways like hemodynamic, metabolic, and inflammatory pathways. Increase in reactive oxygen species formation induced by hyperglycemia through activation of electron transport chain considered as the initiators in the development of diabetes complications. Prevalence of DKD is raising continuously with disparate growth in low to middle-income countries and under-recognized as a global burden of disease. DKD imposes an enormous humanistic, economic, and societal burden. DKD in the initial stage is often undiagnosed until the manifestations of serious complications. The major hurdle in the early diagnosis is limited knowledge, unroutine screening. Timely diagnosis and appropriate interventions are the best approaches to deal with this catastrophic condition. Early diagnosis can have lifetime benefits by controlling the progression of the disease, increasing life expectancy, decreasing the humanistic and economic burden. Even after all these benefits; DKD cases are diagnosed when the condition worsens. Non-availability of potential diagnostic biomarkers is the main barrier to the early diagnosis of DKD. The present review highlights the worldwide prevalence, risk factors, and potential biomarkers for the early detection of DKD.